2018
DOI: 10.1111/rda.13373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐density lipoprotein on oocyte maturation and bovine embryo development in vitro

Abstract: High‐density lipoprotein (HDL) is the main lipoprotein in the follicular fluid, and it has anti‐inflammatory, antioxidant and cryoprotectant properties. The anti‐inflammatory potential and antioxidant potential are derived from its lipid composition, especially the apolipoprotein AI (ApoAI) and paraoxonase 1 (PON1). The aim of this study was to evaluate the effect of HDL during in vitro maturation (IVM) on oocyte maturation and early bovine embryo development. For this, cumulus–oocyte complexes (COCs) were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Heifers in group 2FG showed lower levels of high-density lipoprotein than those that had not received gluconate. High-density lipoprotein has anti-inflammatory and anti-oxidant properties [58], and higher levels may reflect a reaction to stress. Indeed, high-density lipoprotein levels increased across all four groups during the stressful situation of transfer into open-door pens.…”
Section: Discussionmentioning
confidence: 99%
“…Heifers in group 2FG showed lower levels of high-density lipoprotein than those that had not received gluconate. High-density lipoprotein has anti-inflammatory and anti-oxidant properties [58], and higher levels may reflect a reaction to stress. Indeed, high-density lipoprotein levels increased across all four groups during the stressful situation of transfer into open-door pens.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the addition of antioxidants, the in vitro embryos development still undergoes ROS-mediated oxidative stress ( 54 ). Some studies show that culture medium with correct dose of antioxidants protects embryos from oxidative stress ( 51 , 52 , 53 ); however some contrasting evidence has also been presented ( 55 , 56 ). Overall, it is necessary to control the oxidative stress conditions of embryos to have increased in vitro embryo quality.…”
Section: Discussionmentioning
confidence: 99%
“…APOH and APOM are also associated with HDL function [ 53 ]. It has been reported that abnormal metabolism of HDL and its lipoprotein mutation affect fertility in females and also affect the maturation and embryo quality of oocytes matured in vitro [ 54 , 55 , 56 , 57 ]. HDL is the only major lipoprotein detected in follicular fluid, and HDL plays an important role in ovarian cholesterol transport [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those reported for the ovarian proteome of ewes with different genotypes of FecB [ 19 ], suggesting that FecB mutant ewes can provide sufficient cholesterol for follicle development and thus produce more ovulated oocytes. It has been shown that increased paraoxonase 1 (PON1) and APOA1 can enhance the resistance of bovine oocytes to oxidative stress and improve embryo survival after in vitro fertilization and maturation of oocytes [ 57 , 64 ]. In the present study, it was found that PON1 and APOA1 were clustered in cluster 6, and the abundances of these proteins were significantly higher in both BB and WB types than in wild-type ewes.…”
Section: Discussionmentioning
confidence: 99%